Minocycline Mitigation of Tremor Syndrome and Defect of Cognitive and Balance Induced by Harmaline - Marzieh Maneshian; Farinaz Nasirinezhad; Fatemeh Mohammadi; Mina Behzadi; Majid Asadi-Shekaari; Mohammad Shabani (Basic and Clinical Neuroscience, 2021)
Introduction: Minocycline has anti-inflammatory, anti-apoptotic, and anti-oxidant effects. Preclinical data suggest that minocycline could be beneficial for treating common neurological disorders, including Parkinson disease and multiple sclerosis. Methods: In this study, the effects of minocycline on harmaline-induced motor and cognitive impairments were studied in male Wistar rats. The rats were divided into four groups of ten animals each. Harmaline was used for the induction of Essential Tremor (ET). Minocycline (90 mg/kg, IP) was administered 30 minutes before the saline or harmaline. Tremor intensity, spontaneous locomotor activity, passive avoidance memory, anxiety-related behaviors, and motor function were assessed in the rats. Results: The results showed that minocycline could recover tremor intensity and step width but failed to recuperate the motor balance. The memory impairments observed in harmaline-treated rats were somewhat reversed by administration of minocycline. The cerebellum and inferior olive nucleus were studied for neuronal degeneration using histochemistry and transmission electron microscopy techniques. Harmaline caused ultrastructural changes and neuronal cell loss in inferior olive and cerebellar Purkinje cells. Minocycline exhibited neuroprotective changes on cerebellar Purkinje cells and inferior olivary neurons. Conclusion: These results open new therapeutic perspectives for motor and memory impairments in ET. However, further studies are needed to clarify the exact mechanisms.